NECA alleviates inflammatory responses in diabetic retinopathy through dendritic cell toll-like receptor signaling pathway - Li, Lanjiao; Chen, Jichun; Wang, Zhenyan; Xu, Yan; Yao, Hao; Lei, Wulong; Zhou, Xiyuan; Zheng, Minming (Frontiers in Immunology, 2024)
This study examined the impact of the adenosine receptor agonist 5'-(N-ethylcarboxamido)-adenosine (NECA) in the peripheral blood of healthy individuals, those with diabetes mellitus, diabetic retinopathy (DR), and C57BL/6 mice, both in vivo and in vitro. Flow cytometry (FCM) and Enzyme linked immunosorbent assay (ELISA) showed that NECA inhibited the expression of surface markers of dendritic cells (DCs) and bone-marrow-derived dendritic cells (BMDCs), increased anti-inflammatory cytokines and decreased proinflammatory cytokines. Polymerase chain reaction (PCR) and western blot (WB) showed that NCEA decreased mRNA transcription and protein expression in the TLR-4-MyD88-NF-κB pathway in DCs and BMDCs. The DR severity in streptozocin (STZ) induced diabetic mice was alleviated. NECA-treated DCs and BMDCs were co-cultivated with CD4+T cells, resulting in modulation of Treg and Th17 differentiation, along with cytokine secretion alterations. In summary, NECA could impair DCs' ability to present antigens and mitigate the inflammatory response, thereby alleviating the severity of DR.